2021
DOI: 10.7150/jca.54650
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of drug-eluting bead transarterial chemoembolization with CalliSpheres® microsphere for hepatocellular carcinoma with portal vein tumor thrombus: a preliminary study

Abstract: Objective : To prospectively evaluate the safety and therapeutic effectiveness of drug-eluting beads transcatheter arterial chemoembolization (DEB-TACE) with CalliSpheres® microsphere (CSM) for the treatment of hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT), and to analyze the prognostic factors. Method : Between November 2015 and November 2017, consecutive 58 HCC patients with PVTT who received DEB-TACE with CSM treatment were prospectively enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…A most recently published study demonstrated that the higher Child-Pugh classification and liver tumor burden were independent prognostic factors associated with poor survival for HCC patients with PVTT treated by DEB-TACE. 26 Interestingly, these significant risk factors revealed by their study were consistent with another retrospective study conducted by Gorodetski et al, 9 but not with ours. The reasons for this discrepancy might be that the sample sizes for these 2 studies were relatively small with only 58 and 38 patients enrolled, respectively, and no validations were performed to prove the reliability of their results.…”
Section: Discussionsupporting
confidence: 90%
“…A most recently published study demonstrated that the higher Child-Pugh classification and liver tumor burden were independent prognostic factors associated with poor survival for HCC patients with PVTT treated by DEB-TACE. 26 Interestingly, these significant risk factors revealed by their study were consistent with another retrospective study conducted by Gorodetski et al, 9 but not with ours. The reasons for this discrepancy might be that the sample sizes for these 2 studies were relatively small with only 58 and 38 patients enrolled, respectively, and no validations were performed to prove the reliability of their results.…”
Section: Discussionsupporting
confidence: 90%
“…Initiation and follow-up of treatment were carried out at one of four centers, with baseline dynamic contrast-enhanced computed tomography (CT) imaging obtained within 7 days before treatment. PVTT was confirmed by enhanced CT or enhanced Magnetic Resonance Imaging (MRI), the imaging features of PVTT included solid lesions within the portal vein in all the phases of intravenous enhanced 3-phase computed tomography, especially with an enhancement of contrast in the arterial phase and washout in the portal venous phase of the procedure ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…As has previously been reported ( 22 ), TACE was performed by administering doxorubicin mixed with 5–20 mL lipiodol (Lipiodol Ultrafluide, Laboratoire Guerbet, France) to both groups. The dose of doxorubicin was 50–75 mg/m 2 (Haizheng Pharmaceutical Co. Ltd., China) adjusted based on patient liver function, tumor size, vascularity, presence of an arterioportal shunt, and body surface area.…”
Section: Methodsmentioning
confidence: 99%
“…Also the combination of DEB-TACE with microsphere in HCC patients with PVTT has been reported safe, well tolerated and with promising preliminary clinical outcomes (the survival rate at 6, 12, 18, and 24 months was 72.4,% 41.4%, 22.4%, and 19%, respectively). 143 …”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%